The Performative Movements of Deisiane Barbosa - Cunha, Rubens da (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
Deisiane Barbosa is an artist from Recôncavo Baiano who creates a multimodal artistic work including poetry, letter writing, performances, visual arts, photography, sewing, and book editing. Her work fuses artistic languages to challenge established categories and promote the creation of counter-narratives. Ancestry, memory, and feminism are central themes in her work, which echo the experiences of Black women. This study discusses three long-term artistic projects (referred to here as performative movements): Cartas a Tereza, Andarilha Edições, and Casamendoeira. Cartas a Tereza involves letter writing, performances, video art, and urban interventions. Andarilha Edições is a publishing house that specializes in handsewn books and that values the book as an aesthetic object. Casamendoeira is the reconstruction of Deisiane’s grandparents’ old house. The house has been transformed into a cultural center and an artist’s’ residence. It is also the subject of a narrative of the same name.